2013
DOI: 10.1007/s10661-013-3294-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation kinetics of tetraconazole in three types of soil and water under laboratory condition

Abstract: Laboratory experiment was conducted to understand the persistence behavior of tetraconazole in three soils of West Bengal (alluvial, red lateritic, and coastal saline) and also in water maintained at three different pH (4.0, 7.0, and 9.2) conditions. Processed soil samples (100 g) were spiked at two treatment doses: 2.5 μg/g (T₁) and 5.0 μg/g (T₂). Double distilled buffered water (200 ml) was spiked at two treatment doses: 1.0 μg/ml (T₁) and 2.00 μg/ml (T₂). The tetraconazole dissipation followed first-order r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…Both half‐lives were shorter than those reported by Alam et al . () for tetraconazole in soil (66.9–86 days). This difference could be attributed to variations in the organic carbon content of the tested soils, which was somewhat higher in our samples (1.5%) than in those of Alam (0.5–1.21%).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Both half‐lives were shorter than those reported by Alam et al . () for tetraconazole in soil (66.9–86 days). This difference could be attributed to variations in the organic carbon content of the tested soils, which was somewhat higher in our samples (1.5%) than in those of Alam (0.5–1.21%).…”
Section: Resultsmentioning
confidence: 97%
“…Our findings and those of Alam et al . () were shorter than those reported for propiconazole (200 days; Thorstensen and Lode, ) and for flutriafol, epoxiconazole and triadimenol (more than 2 years; Singh, ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…World Health Organization (WHO) classified clofentezine as the slightly hazardous category III [6]. Alam and Kole [7] reported that hydrolysis was the major dissipation pathway of clofentezine. It can be digested more quickly under alkaline conditions of pH 9.2 with a low half-life value of 0.53 day.…”
Section: Introductionmentioning
confidence: 99%